Optimizing Local Wisdom-Based Ecotourism Development: Village Community Economic Transformation Through Gili Iyang Tourism Development - Zaifuddin Razti; Zainal Muttaqin; Idris Idris (Department of Tadris IPS FITK IAIN Syekh Nurjati Cirebon, 2022)
Abstract: This paper discusses optimizing the development of ecotourism based on local wisdom on Gili Iyang Island, Sumenep. Methodologically, the type of research used in this research is descriptive qualitative, with data collection techniques of literature study (reading books, journals, magazines, newspapers, documents, and other media information that has to do with being researched). In addition, researchers also conducted observations and interviews. The results show that tourism potential has not been utilized as an opportunity to improve the welfare of the community. All aspects are still in the medium and low categories, so it can be said that they are not optimal. Therefore, environmental conservation is very important so that tourism objects on Gili Iyang can develop. In this case, the concept of tourism that is in line with the role of environmental conservation is ecotourism.Keywords: Ecotourism, Tourism, Local Wisdom, Optimization of Development Abstrak: Tulisan ini membahas tentang optimalisasi pengembangan ekowisata berbasis kearifan lokal di Pulau Gili Iyang, Sumenep. Secara metodologis, jenis penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif, dengan teknik pengumpulan data studi kepustakaan (membaca buku, jurnal, majalah, surat kabar, dokumen-dokumen, serta media informasi lain yang ada hubungannya dengan yang diteliti). Selain itu, peneliti juga melakukan observasi dan wawancara. Hasil penelitian menunjukkan bahwa potensi wisata belum dimanfaatkan sebagai peluang dalam meningkatkan kesejahteraan masyarakat. Semua aspek masih dalam kategori sedang dan rendah, sehingga dapat dikatakan belum maksimal. Karena itu, konservasi lingkungan sangat penting dilakukan supaya objek wisata di Gili Iyang berkembang. Dalam hal ini, konsep wisata yang selaras dengan peran konservasi lingkungan adalah ekowisata.Kata kunci: Ekowisata, Pariwisata, Kearifan Lokal, Optimalisasi Pengembangan